Math, asked by kumarharsh62828, 2 months ago

f a+b+c = 0, then a^3 + b^3 + c^3 is

Answers

Answered by DarkShadow197
0

Answer:

Step-by-step explanation:

Given that,

if a+b+c=0 then a  

3

+b  

3

+c  

3

 

We know that,

a  

3

+b  

3

+c  

3

=(a+b+c)[a  

2

+b  

2

+c  

2

−ab−bc−ca]+3abc

Put, a+b+c=0

 a  

3

+b  

3

+c  

3

=0.[a  

2

+b  

2

+c  

2

−ab−bc−ca]+3abc

a  

3

+b  

3

+c  

3

=3abc

Answered by jishudey510
0

formula a^3+b^3+c^3=(a+b+c)(a^2+b^2+c^2-ab-bc-ac)

a^3+b^3+c^3

=(a+b+c)(a^2+b^2+c^2-ab-bc-ac)

=0×a^2+b^2+c^2-ab-bc-ca

=0

ans =0

Similar questions